2020
DOI: 10.1002/marc.202000195
|View full text |Cite
|
Sign up to set email alerts
|

The Role of α, γ,  and Metastable Polymorphs on Electrospun Polyamide 6/Functionalized Graphene Oxide

Abstract: The present paper describes the addition of nitroxide‐functionalized graphene oxide (GOFT) into polyamide 6 (PA6) micro‐ and nanofibers, which are obtained through electrospinning. Scanning electron microscopy micrographs demonstrate the presence of fibers. Tensile testing presents an unexpected and non‐obvious behavior, in which the Young's modulus, tensile strength, and elongation simultaneously and remarkably increase compared to the pristine polymer nanofibers. GOFT induces the hydrogen bonding between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Reinforcement in mechanical properties were associated to the hydrogen bond between the NH group from PA-6 with the functional groups in the graphene. 30 Strong interaction between PA-6 filled with organically modified zirconium phosphate was reported by Garcia et al 31 and Freitas et al 27 We attributed the lowering of the amine index to the action of ZrP collapsing of the intra and inter PA-6 hydrogen bond. We also believed that this breakage favored the formation of hydrogen bond among P-OH groups in ZrP with PA-6 carbonyl groups.…”
Section: Resultsmentioning
confidence: 66%
“…Reinforcement in mechanical properties were associated to the hydrogen bond between the NH group from PA-6 with the functional groups in the graphene. 30 Strong interaction between PA-6 filled with organically modified zirconium phosphate was reported by Garcia et al 31 and Freitas et al 27 We attributed the lowering of the amine index to the action of ZrP collapsing of the intra and inter PA-6 hydrogen bond. We also believed that this breakage favored the formation of hydrogen bond among P-OH groups in ZrP with PA-6 carbonyl groups.…”
Section: Resultsmentioning
confidence: 66%
“…Based on the SEM analysis above and the changes in the mechanical properties of PA10T/ND nanocomposites, it is found that the introduction of ND has a significant reinforcing effect on the composites. The reinforcement effect is not only due to the homogeneous dispersion of ND in the matrix, but also a result of the formation of the hydrogen bonds and amide bonds between the surface oxygen groups of ND and the PA10T matrix, which provides strong interactions between the ND and PA10T 33,34 . When the ND content increased, the agglomeration of ND intensified.…”
Section: Resultsmentioning
confidence: 99%
“…The reinforcement effect is not only due to the homogeneous dispersion of ND in the matrix, but also a result of the formation of the hydrogen bonds and amide bonds between the surface oxygen groups of ND and the PA10T matrix, which provides strong interactions between the ND and PA10T. 33,34 When the ND content increased, the agglomeration of ND intensified. These agglomerated ND particles acted as crosslinking points and caused nanocomposites networks to form with strengthened intermolecular forces between polymer chains.…”
Section: Mechanical Properties Of 10 T/nd Nanocompositesmentioning
confidence: 99%
“…Figure 3(a) shows the FTIR spectra of nanofibers prepared by varying the weight percentages of nylon-6. The N-H stretching of nylon-6 exhibits the characteristic features of a polyamide, displaying a peak at 3309 cm −1 and a secondary peak at 3075 cm −1 [16,23,24]. The peak corresponding to the aliphatic C-H stretching vibration in the polymer chain was observed at 2933 cm −1 in nylon-6 samples.…”
Section: Morphological Structural and Thermal Analyses Of Nylon-6 Nan...mentioning
confidence: 95%